Assessment of Innovation and Investment Activities in The Context of Digital Transformation - Irina ERSHOVA; Aleksandr Sotnikov; Elizaveta Ershova; Elena Belyaeva (Communications of International Proceedings, 2021)
The relevance is due to the need for technological modernization of production facilities, the development of innovative and competitive products on the world market, and an increase in non-resource non-energy exports. Attraction of investments is also aimed at obtaining new technologies and R&D results (participation in joint R&D, obtaining rights to key results of intellectual activity and creating our own results of intellectual activity), gaining access to foreign markets, creating new high-tech jobs and improving the qualifications of personnel. The result of the implementation of the task of attracting investment is the creation and modernization of domestic industries, built into the value chain in the world market and having a scientific and technical groundwork for R&D. Currently, there are a number of theoretical approaches to the content and organization of work on the preparation of the mechanism for the formation and implementation of innovation and investment policy, as well as practical experience summarized by various scientists and practitioners. The effectiveness of the use of innovation and investment potential in Russia as a whole depends on the innovation and investment potential of meso-economic systems at the meso-level. When assessing the innovation potential at the meso-level, the level of human development, the assessment of scientific knowledge, the application and implementation of new knowledge, and the possibility of creating know–how are taken into account. The assessment of the innovation potential of the meso-level is important for the justification of innovation and investment policy and the development of regional development programs, taking into account the effective use of innovation and investment resources of the meso-economic system.
Keywords: Innovation Activities; Investment Activities; Digital Transformation